Mission accomplished : on founding constitutional adjudication in Central Europe - Procházka, Radoslav (Central European University Press, 2002)
Examines constitutional jurisdiction in the so-called Visegrad Four: Poland, Hungary, the Czech Republic and Slovakia. The creation of constitutional courts was one of the major milestones in the re-creation of the democratic system in these countries. In Europe constitutional courts exert much of the functions of the Supreme Court of the US. However, the immediate western European samples showed marked differences, which is why besides similarities, the theory and practice of constitutional law show differences in these four countries. Procházka analyses and explains these similarities and differences. Mission Accomplished contributes to the literature on comparative constitutional law by offering insights into the constitutional discourses that go beyond the discussion of notorious cases and events in these four countries. Procházka argues that the various historical, cultural, socio-psychological, political and institutional contexts have translated into different modes of constitutional adjudication and interpretation.